Variable immune cell frequencies in peripheral blood of LEW.1AR1-iddm rats over time compared to other congenic LEW strains - Arndt, T (Blackwell Science Inc, 2014)
The LEW.1AR1-iddm rat is an animal model of human type 1 diabetes (T1D), which arose through a spontaneous mutation within the major histocompatibility complex (MHC)-congenic background strain LEW.1AR1. The LEW.1AR1-iddm rat is characterized by two phenotypes: diabetes development with a diabetes incidence of 60% and a variable T cell frequency in peripheral blood. In this study the immune cell repertoire of LEW.1AR1-iddm rats was analysed over time from days 30 to 90 of life and compared to the background strain LEW.1AR1 and the LEW rat strain as well as the LEW.1WR1 rat strain. The LEW.1AR1-iddm rats are characterized by a high variability of CD3(+), CD4(+) and CD8(+) T cell frequencies in peripheral blood over time, and the frequency is unique for each animal. The variability within the frequencies resulted in changes of the CD4(+) : CD8(+) T cell ratio. The other three rat strains studied were characterized by a stable but nevertheless strain-specific T cell frequency resulting in a specific CD4(+) : CD8(+) T cell ratio. The frequency of natural killer (NK) cells and B cells in LEW.1AR1-iddm rats was increased, with a higher variability compared to the other strains. Only monocytes showed no differences in frequency and variability between all strains studied. These variabilities of immune cell frequencies in the LEW.1AR1-iddm rats might lead to imbalances between autoreactive and regulatory T cells in peripheral blood as a prerequisite for diabetes development.